Spark plasma sintering of bulk SrAl2O4-Sr3Al2O6 eutectic glass with wide-band optical window. (13th April 2018) - Liu, Jiaxi; Lu, Nan; He, Gang; Li, Xiaoyu; Li, Jianqiang; Li, Jiangtao
Abstract: SrAl2 O4 -Sr3 Al2 O6 eutectic glass was prepared by using an aerodynamic levitator equipped with a CO2 laser device. A bulk transparent amorphous sample was obtained by the spark plasma sintering (SPS) of the prepared eutectic glass. XRD, a UV–vis-NIR spectrophotometer and FT-IR were employed to characterize the phase evolution and optical properties. The results show that the bulk SrAl2 O4 -Sr3 Al2 O6 samples fabricated by the containerless process and SPS between 852 °C–857 °C were fully amorphous. The amorphous sample has a wide transparent window between 270 nm and 6.2 μ m. The average refractive index in the visible light region is 1.680 and the Abbe number is 27.4. The prepared bulk SrAl2 O4 -Sr3 Al2 O6 eutectic glass with the wide-band optical window may be a promising candidate for optical applications.